Concepts for Prehospital and Initial In-hospital Therapy of Status Epilepticus - Strzelczyk, Adam; Kay, Lara; Kellinghaus, Christoph; Knake, Susanne; von Blomberg, Anemone; Willems, Laurent M.; Rosenow, Felix (Neurology International Open, 2017)
Status epilepticus is a major neurological emergency requiring immediate anticonvulsive treatment. Rapid and sufficient treatment is essential for optimizing outcome and reducing mortality. Here, we give an overview on concepts for acute prehospital and initial in-hospital treatment of status epilepticus. Options for initial therapy in settings without intensive care monitoring are presented in detail.